COVID-19 Infection Among Healthcare Workers: Serological Findings Supporting Routine Testing - Stock, Ariel D.; Bader, Edward R.; Cezayirli, Phillip; Inocencio, Julio; Chalmers, Samantha A.; Yassari, Reza; Yanamadala, Vijay; Eskandar, Emad (Frontiers in Medicine, 2020)
A growing body of evidence demonstrates that asymptomatic and pre-symptomatic transmission of SARS-CoV-2 is a major contributor to the Covid-19 pandemic. Frontline healthcare workers in Covid-19 hotspots have faced numerous challenges, including shortages of personal protective equipment (PPE), and difficulties acquiring clinical testing. The magnitude of healthcare workers’ exposure and the potential for asymptomatic transmission makes it critical to understand the incidence of infection in this population. To determine the prevalence of asymptomatic SARS-CoV-2 infection amongst healthcare workers, we studied frontline staff working in the Montefiore Health System in New York City. All participants were asymptomatic at the time of testing, and were tested by RT-qPCR and for anti-SARS-CoV-2 antibodies. Participants’ medical, occupational, and Covid-19 exposure histories were recorded via questionnaires. Of the 98 asymptomatic healthcare workers tested, 19 (19.4%) tested positive by RT-qPCR and/or ELISA. Within this group, 4 (4.1%) were RT-qPCR positive and 4 (4.1%) were PCR and IgG positive. Notably, an additional 11 (11.2%) individuals were IgG positive, without a positive PCR. Two PCR positive individuals subsequently developed Covid-19 symptoms, while others remained asymptomatic at two-week follow-up. These results indicate that there is considerable asymptomatic infection with SARS-CoV-2 within the healthcare workforce, despite current mitigation policies. Furthermore, presuming that asymptomatic staff are not carrying SARS-CoV-2 is inconsistent with our results, and could result in amplified transmission within healthcare settings. Consequently, aggressive testing regiments, such as testing frontline healthcare workers on a regular, multi-modal basis may be required to prevent further spread within the workforce and to patients.